Flash Bottom‐Up Arc Synthesis of Nanocarbons as a Universal Route for Fabricating Single‐Atom Electrocatalysts (Small Methods 8/2021). Issue 8 (12th August 2021) - Jung, Jae Young; Jang, Jue‐Hyuk; Kim, Jeong‐Gil; Lee, Kug‐Seung; Lim, Hyung‐Kyu; Kim, Pil; Chang, Robert P. H.; Park, Ji‐Woong; Yoo, Sung Jong; Kim, Nam Dong
Abstract : Inside Back Cover In the article number 2100239, Yoo, Kim, and co‐workers report a universal strategy for fabricating single‐atom catalysts (SACs) using a flash bottom‐up arc discharge. It allows simultaneous incorporation of metal atoms into a carbon lattice during formation of nanocarbons. It is applicable to various metals and nanocarbons.